Development of virtual laboratories in engineering with the participation of undergraduate students - Pérez Hernández, Miguel M. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Covid-19 pandemic changed the way engineering laboratories are managed. For the last quarter of 2020, the development of practices in the Virtual Processes Laboratory involving undergraduate Chemical Engineering students from the Metropolitan University was established as an academic objective, using the programming and numerical calculation platform Matlab, applying the methodology of study called Project Based Learning. The students’ response indicated that the experience gained gave them confidence in its use, a better understanding of the associated advantages and disadvantages, and in the future a competitive benefit in the industry.